Development and usability of VRainSUD’s cognitive training virtual reality platform for substance use disorders - Tânia Caetano; Maria Salomé Pinho; Hugo Freire; Dany Mota; Eduardo Ramadas; Jessica Lopes; Filipa Freire-Santos; Maria dos Anjos Dixe (Scientific Reports)
Abstract Cognitive deficits have been shown to increase the likelihood of relapse in individuals with substance use disorders (SUD). As such, cognitive training programs are important interventions for this population. In this study, we describe the development and test the usability of a virtual reality (VR)-based cognitive training program for individuals with SUD – VRainSUD. A total of 17 patients receiving inpatient treatment for SUD at an Addiction Treatment Center agreed to participate in the study. Participants completed 9 tasks designed to test the platform’s usability. The key performance indicators (e.g., time to complete the task) as well as any relevant observations were recorded. Finally, each participant completed a brief survey and the Post-Study System Usability Questionnaire (PSSUQ). VRainSUD was considered easy and pleasant to use but additional instructions were required on certain cognitive training tasks. The total PSSUQ score confirmed an overall high level of satisfaction concerning the platform’s usability (2.72 ± 1.92). Among the three subscales, system usefulness presented the most satisfactory score (1.76 ± 1.37) and information quality presented the least satisfactory score (3.00 ± 1.95). Changes were made to the platform to improve the on-screen information and instructions. Overall, participants showed interest in integrating VRainSUD into their standard treatment. Despite limited prior VR experience, they quickly adapted to the controllers and navigation. VRainSUD can be a potentially successful add-on to SUD treatment.